Hedonic price analysis for consumer preference on rice quality attributes in some selected state of North Western Nigeria - Abubakar, Bello Bunza; ABDULLAH, Abubakar Ngaski; JABO, Muhammad Sani Muhammad (International Journal of Sustainable Agricultural Research, 2025)
In Nigeria, rice consumption has significantly increased, particularly among urban populations. The country is the leading producer and consumer of rice in West Africa, with demand expected to rise due to population growth, urbanization, and changing dietary preferences. This study examined the influence of rice characteristics on pricing by analyzing 156 rice samples from 15 markets within a 400 km radius of the Middle Rima River Valley Irrigation Scheme. The hedonic price analysis of various rice types revealed that certain markets offered substantial price reductions, while consumers exhibited a willingness to pay a premium for imported rice. Although domestic rice possesses superior nutritional quality, characterized by higher amylose and protein content, consumers preferred imported rice due to its more appealing physical attributes. Key desirable qualities included a low percentage of broken grains, a high length-to-width ratio, minimal varietal mixing, and reduced impurities. To reduce the price disparity between domestic and imported rice, improvements in post-harvest handling and processing are crucial to enhance the physical characteristics of local varieties. Additionally, increased advocacy is necessary to emphasize the nutritional benefits of domestic rice and promote consumer preference for locally produced options.